The white lupin CCR1 receptor-like kinase controls systemic Autoregulation of Cluster Root and Nodule Development - Laurence Marquès; Fanchon Divol; Alexandra Boultif; Fanny Garcia; Alexandre Soriano; Cléa Maurines-Carboneill; Virginia Fernandez; Inge Verstraeten; Hélène Pidon; Esther Izquierdo; Bárbara Hufnagel; Benjamin Péret (Proceedings of the National Academy of Sciences, 2025)
Root development is tightly regulated in plants to optimize nutrient acquisition and interactions with soil microorganisms. In legumes, the Autoregulation of Nodulation (AoN) pathway systemically controls the proliferation of root nodules, which are energy-intensive organs. Mutations affecting the AoN pathway result in a hypernodulation phenotype accompanied by altered root development. However, it remains unclear whether this modification of root development is also systemic and coordinated with nodulation. In this study, we report the identification of the constitutive cluster root 1 (ccr1) mutant in white lupin ( Lupinus albus ), which exhibits constitutive production of an excessive number of cluster roots. We demonstrate that CCR1 is an ortholog of HAR1/SUNN/NARK leucin-rich repeat-receptor like kinases (LRR-RLKs), which are key regulators of the AoN pathway. Furthermore, we show that CCR1 negatively regulates both nodule and cluster root development. Interspecific grafting experiments between white and narrow-leaved lupin ( Lupinus angustifolius ), a species incapable of producing cluster roots, show that ccr1 shoots can induce the formation of cluster-like roots in narrow-leaved lupin rootstocks. This highlights the conservation of a CCR1-dependent signaling cascade. Transcriptome analyses reveal that CCR1 targets the conserved NIN/LBD16-NFYA regulatory module, which connects nodule and lateral root development through a shared inhibitory systemic pathway. We propose that this pathway represents a broader developmental control mechanism of root organogenesis, termed Autoregulation of Cluster Root and Nodule Development (AoDev).